2002
DOI: 10.1021/cr010122p
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Organic Reactions in Water

Abstract: Ulf Lindstro ¨m was born in 1971 in Malmo ¨, Sweden. He studied Chemistry and Biology at Lund University to receive his B.Sc. degree in 1996. After earning a licentiate degree in Engineering at Lund Institute of Technology in 1998, he moved to Stockholm University to complete his doctoral thesis in 2000 under the supervision of Professor Peter Somfai. His Ph.D. work mainly concerned the development of new methods of preparing optically active nitrogen heterocycles. He then moved to California and Stanford Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
504
1
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,634 publications
(522 citation statements)
references
References 197 publications
4
504
1
13
Order By: Relevance
“…However, since Breslow´s work in early 1980s, [79] many studies have shown that the Diels-Alder reaction often proceeds faster and with higher selectivity in water than in organic medium. [80][81][82][83] The origin for the water rate acceleration effect, although lacking complete understanding, seems to relay mainly on two effects: enforced hydrophobic interactions and activation of the dienophile by hydrogen bonding with water molecules.…”
Section: Diels-alder Reactions In Aqueous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…However, since Breslow´s work in early 1980s, [79] many studies have shown that the Diels-Alder reaction often proceeds faster and with higher selectivity in water than in organic medium. [80][81][82][83] The origin for the water rate acceleration effect, although lacking complete understanding, seems to relay mainly on two effects: enforced hydrophobic interactions and activation of the dienophile by hydrogen bonding with water molecules.…”
Section: Diels-alder Reactions In Aqueous Mediamentioning
confidence: 99%
“…[84] Hydrogen bonding between water and the activating group of the dienophile (frequently a carbonyl group) is likely to be also responsible for the rate acceleration. [80][81][82][83] Similarly to the way Lewis acids activate Diels-Alder reactions in organic solvents, the water molecules coordinate with the carbonyl group to form an activated dienophile that is more electrophilic and thus more reactive towards cycloaddition with dienes ( Figure 14). …”
Section: Diels-alder Reactions In Aqueous Mediamentioning
confidence: 99%
“…Instead, surfactanttype protonic acids such as dodecylbenzenesulfonic acid (DBSA) are useful. 26,28,30) Here, we report that the cyclization reaction proceeds in good yield using DBSA as a surfactanttype protonic acid catalyst.…”
mentioning
confidence: 87%
“…Although homogeneous catalysts work very well, their industrial applications are limited by both tedious work-up and non-trivial separation procedures, which may lead to contamination of the final product. In addition, homogeneous catalysts suffer from short lifetimes resulting in poor recyclability, which may increase cost and lead to heavy-metal pollution in water (6,7). Solid-supported homogeneous organometallic catalysts could effectively circumvent this issue.…”
Section: Introductionmentioning
confidence: 99%